Epidemiology and potential associated risk factors of drug-related problems in hospitalised children in UK. Issue 6 (9th May 2013) - Rashed, A; Tomlin, A; Jackman, J; Neubert, A; Wilton, L; Wong, I
Abstract : Aim: Drug-related problems (DRP) are 'an event or circumstance involving drug therapy that actually or potentially interferes with the desired health outcome'. 1 Data on the extent and characteristics of DRPs in children in the UK are limited. Our aim was to determine the epidemiology of and identify risk factors for DRPs in hospitalised children. Methods: A prospective cohort study in children aged 0–18 years, admitted to the medical ward, paediatric intensive care unit (PICU), and neonatal intensive care unit during a three-month period at a paediatric hospital in the UK. Patients' charts, medical records and laboratory data were reviewed daily to identify DRPs; their preventability and severity were assessed. Logistic regression was used to analyse the potential risk factors associated with DRP incidence. Results: 373 children (median age 1.4 years, Interquartile range 3 months–7 years, 59.5% male) were included. 147 patients suffered from 220 DRPs and the overall DRP incidence was 39.4% (95% CI 34.4 to 44.6). Incidence was highest in PICU 60.0 (95% CI 45.2 to 73.6). Dosing problems were the most frequently reported DRPs (n=76, 34.5%). 67.7% of DRP (n=149) cases were preventable; 77.7% (n=171) of DRPs were assessed as minor; 22.3% (n=49) as moderate. Morphine and salbutamol were most frequently involved in DRPs (7.7% n=17/220, 6.4% n=14/220, respectively). Number of prescriptions (≥5) and presence of disease of respiratory system were strong predictors for DRPs occurrence in children (OR 2.3, 95% CI 1.4 to 3.6; OR 2.3, 95% CI 1.1 to 5.0, respectively; p<0.05). Conclusions: DRPs were common in the hospitalised children in this study; the most frequent were dosing problems; the majority of them were preventable. Polypharmacy and presence of respiratory system diseases were strong predictors of DRPs. The high percentage of preventable DRPs emphasises the importance of providing more training to healthcare professionals in the prescribing and use of medicines in children to minimise the risk of DRPs.